Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernández-Llario, P; Mateos-Quesada, P; Silvério, A; Santos, P (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernandez-Llario, P.; Mateos-Quesada, P.; Silvério, A.; Santos, P. (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar